2021
DOI: 10.1101/2021.06.11.448058
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential growth is a critical determinant of zebrafish pigment pattern formation

Abstract: The skin patterns of vertebrates are formed by complex interactions between pigment-producing cells during development. Adult zebrafish (Danio rerio), a model organism for investigating the underlying patterning processes, display alternating horizontal blue and golden stripes, generated by the self-organisation of three pigment cell-types. Mathematical studies in which these cells are modelled as individual agents communicating via short- and long-range interactions have produced breakthroughs in the understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…However, it was later shown that the interactions between the pigment cells were regulated by cell projections instead of diffusion (Eom et al 2015;Mahalwar et al 2014) and that therefore, while the criteria for local activation and long-range inhibition still held, it did not fit the traditional reaction-diffusion requirements of a true Turing pattern (Watanabe & Kondo 2015a,b). Even more recently, it has been suggested that growth of the tissue is important for stripe formation as well (Owen et al 2021). This pattern could thus be said to be formed by a 'Turing-like' mechanism, where cell motion takes the role of molecular diffusion in the original Turing mathematical model.…”
Section: Turing Patterns In Biological Systemsmentioning
confidence: 99%
“…However, it was later shown that the interactions between the pigment cells were regulated by cell projections instead of diffusion (Eom et al 2015;Mahalwar et al 2014) and that therefore, while the criteria for local activation and long-range inhibition still held, it did not fit the traditional reaction-diffusion requirements of a true Turing pattern (Watanabe & Kondo 2015a,b). Even more recently, it has been suggested that growth of the tissue is important for stripe formation as well (Owen et al 2021). This pattern could thus be said to be formed by a 'Turing-like' mechanism, where cell motion takes the role of molecular diffusion in the original Turing mathematical model.…”
Section: Turing Patterns In Biological Systemsmentioning
confidence: 99%